MEMBANGUN KELUARGA YANG SEJAHTERA, DAMAI DAN BERTAKWA - Fajarwati (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2020)
Every couple desires a prosperous, peaceful and godfearing home. Let a family create a household as the Prophet (peace and blessings of Allaah be upon him) suggested. With the creation of a household like this, every family member will feel happy, happy, safe, loving each other, looking after each other. Every family member is always called to go home, because the house is not just a shelter when it is raining and hot. But the house is a place of calming the restless heart, a place of family coaching and a place to cultivate inner bonds between its inhabitants. That way arranges the household so beautifully to please all the family members.